The Impact of Madrasah Principals’ Servant Leadership Style on Teachers’ Work Ethic: An Empirical Study in South Lampung - andari, An An (JURNAL AL-TANZIM, 2025)
This study aims to examine the influence of the principal's servant leadership style on the work ethic of teachers in madrasas. This study employed a quantitative approach, utilising a survey method to collect data through questionnaires distributed to 30 teachers. The servant leadership variable was measured using 32 items, while the work ethic variable consisted of 35 items. Descriptive analysis showed that teachers' perceptions of the principal's servant leadership style were high (mean score of 126.87 out of 160), as was the work ethic (mean score of 142.93 out of 175). Regression analysis revealed a significant influence between servant leadership and teacher work ethic, with a partial coefficient of determination of 19.80% and a partial correlation coefficient of 0.445. The better the principal's servant leadership style, the higher the teachers' work ethic. These findings suggest that madrasa principals should create a humanistic and productive work environment, and teachers are expected to foster a collaborative work ethic that can enhance the quality of madrasa education.